Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Higher Order Thinking Skills (HOTS) Perbankan Dasar Kelas X SMK - Hanifah Roihanah; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
This development study aims to produce teaching materials in the form of a worksheet based on Higher Order Thinking Skills in basic banking topics for grade X SMK accounting expertise. There are several problems in the curriculum, namely the low competence of teachers brought by the average set by the government, low readiness of student competencies, and limited relevant teaching materials. This research was conducted to solve problems related to very limited teaching materials and will be developed through the Higher Order Thinking Skills (HOTS) Basic Banking Student Activity Sheet (LKPD). The test subjects to be used in this study were 20 students of class X Accounting at SMK Negeri 1 Sambeng Lamongan. The development model that used in this study is 4D Thiagarajan with some stages, they are: define, design, develop, disseminate. But, the was not carried out. The results of this study show that material eligibility 80,5%, evaluation eligibility 81%, language eligibility 77% with the overall eligibility rate is 80% that can be said “feasible”. That teaching materials in the form of the worksheet based on Higher Order Thinking Skills can be used in learning activities.